THE CONCEPT OF BLOCKCHAIN TECHNOLOGY AND ITS OPPORTUNITIES IN THE FIELD OF INFORMATION AND COMMUNICATION TECHNOLOGIES - Zaripova, Shahlo Olimovna (SCIENCE and SOCIETY, 2026)
The article presents the features of the use of blokcheyn technology in information technology. Blokcheyn is a distributed database that does not have storage devices connected to a common server. The goal of the development of blokcheyn is to solve the problem of duplication of spending in cryptocurrency, to provide the possibility of exchange in a low-trust environment without the participation of a third party, to create a distributed transaction register that is resistant to failures, as well as to control the history of transactions. The operation of the blokcheyn and its security are ensured by developers and other blokcheyn participants.
Keywords: Blokcheyn technology; block chain; reliability; cryptocurrency; Torrents P2P mode; information technology; main features of blokcheyn; Bitcoin; transparency; Consensus mechanism; theoretically unlimited peer-to-peer network; "Block" part; decentralization; big data; cryptography